Taschen's New York : hotels, restaurants & shops. - Taschen, Angelika, ....-; McLane, Daisann, ....-; Ober, Poul, ....- (Cologne : Taschen, 2009)
Get the most out of New York In New York, it's all about who you know. And now you're connected. Angelika Taschen knows New York. She's been behind the velvet ropes, explored the secret, unmarked restaurants and beloved neighborhood delis, scoured Soho, Nolita and Tribeca's stylish stores, and scoped out hotels uptown and downtown, from sleek and chic to hidden charms. She provides an all-access pass to parts of New York even most locals don't know. Dictionary-style cutout tabs make it easy to flip through, and a pocket-sized map of Manhattan lists all the shops, hotels, and restaurants in the book. With this guide in hand, New York is yours for the taking. Featuring the Maritime Hotel, a former sailors' dorm, now Chelsea's coolest hotel; Robert De Niro's Greenwich Hotel, with its authentic Japanese spa; the cheap but chic Pod Hotel. Learn how to get the best table at the Waverly Inn, Vanity Fair editor Graydon Carter's exclusive salon for the glitterati; how to find Soho's hidden basement bar subMercer; the Shake Shack, for a terrific burger in the shade of Madison Square Park; Rao's, the Spanish Harlem Italian joint run by the Sopranos' actor who turned Madonna away; where to buy New York's best cheesecake; and Greenwich Letterpress, for hand-printed cards to send to envious friends who didn't make this fabulous New York trip!
Teksten in het Engels, Duits en het Frans.
Keywords: Hotels -- New York (stad).; New York (stad) -- Reisgidsen; Restaurants -- New York (stad).; Winkels -- New York (stad).